Altered Monoamine and Acylcarnitine Metabolites in HIV-Positive and HIV-Negative Subjects With Depression - Cassol, Edana; Misra, Vikas; Morgello, Susan; Kirk, Gregory D; Mehta, Shruti H; Gabuzda, Dana (Journal of acquired immune deficiency syndromes (1999), 2015)
Depression is a frequent comorbidity in HIV infection that has been associated with worse treatment outcomes and increased mortality. Recent studies suggest that increased innate immune activation and tryptophan catabolism are associated with higher risk of depression in HIV infection and other chronic inflammatory diseases, but the mechanisms leading to depression remain poorly understood. The severity of depressive symptoms was assessed by Beck Depression Inventory or Center for Epidemiological Studies Depression Scale. Untargeted metabolomic profiling of plasma from 104 subjects (68 HIV-positive and 36 HIV-negative) across 3 independent cohorts was performed using liquid or gas chromatography followed by mass spectrometry. Cytokine profiling was by Bioplex array. Bioinformatic analysis was performed in Metaboanalyst and R. Decreased monoamine metabolites (phenylacetate, 4-hydroxyphenylacetate) and acylcarnitines (propionylcarnitine, isobutyrylcarnitine, isovalerylcarnitine, 2-methylbutyrylcarnitine) in plasma distinguished depressed subjects from controls in HIV-positive and HIV-negative cohorts, and these alterations correlated with the severity of depressive symptoms. In HIV-positive subjects, acylcarnitines and other markers of mitochondrial function correlated inversely with tryptophan catabolism, a marker of interferon responses, suggesting interrelationships between inflammatory pathways, tryptophan catabolism, and metabolic alterations associated with depression. Altered metabolites mapped to pathways involved in monoamine metabolism, mitochondrial function, and inflammation, suggesting a model in which complex relationships between monoamine metabolism and mitochondrial bioenergetics contribute to biological mechanisms involved in depression that may be augmented by inflammation during HIV infection. Integrated approaches targeting inflammation, monoamine metabolism, and mitochondrial pathways may be important for prevention and treatment of depression in people with and without HIV.